Effectiveness and Cost-Benefit of an Influenza Vaccination Program for Health Care Workers. (1991) - Yassi, Annalee; Kettner, Joel; Hammond, Greg; Cheang, Mary; McGill, Myrna
Abstract : This study retrospectively reviewed the effectiveness of a vaccination program for hospital workers in a large tertiary care hospital, quantified influenza-induced absenteeism, and examined the factors determining the costs and benefits of this program. Absenteeism among high risk hospital workers was increased by 35% (P=0.001) during the virulent influenza epidemic of 1987–88. Benefits, measured as the value of sick time avoided, compared with costs, including materials, occupational nursing staff time, employee time during vaccination, and time lost due to adverse reactions, revealed a net benefit of 39.23 per vaccinated employee. Sensitivity analyses highlighted vaccine efficacy and absenteeism due to influenza and adverse reactions to vaccination as the most important factors; with time lost due to adverse reactions as much as 0.013 days per vaccinated employee and a vaccine efficacy of 70%, net positive benefits could be achieved if influenza-induced absenteeism is 0.5% or greater of paid employee time during the epidemic season. The results suggested that the net cost-benefit of a hospital employee vaccination program to decrease both employee morbidity and nosocomial influenza among patients, would be increased by active promotion of the vaccination program, especially for employees in high risk areas.